Temporal specificity in exercise training - Lieferman, J. A.; Jones, N. A.; Dangelmaier, B. S.; Dedrick, G. S.; Burt, S. E.; Swetmon, J. K.; Hill, D. W. (Medicine & Science in Sports & Exercise, 1995)
Morning and afternoon responses to anaerobic work were measured in college women before and after a training program that was performed at only one time of day. Time to exhaustion and anaerobic capacity were greatest at the time of training. Either training at a particular time of day results in greater adaptations at that time of day, or it influences the phase of the circadian rhythm response to exercise. Implication: The time of day when training is performed affects performance at that time. In serious athletes who compete at specific times in the day/night, the last phase of training should be performed at the same time as the anticipated competitive efforts.